Student-Centered Learning in the Classroom Towards Curriculum Development - Leovigildo Lito Mallillin; Ma. Aurora T. CADAY; Edgardo G. CANDA (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2026)
The study analyzes and evaluates the application of student-centered learning in the classroom, the importance of a student-centered approach for teaching, the promotion and benefits of a student-centered learning environment, and the effectiveness of a student-centered learning approach in teaching. A descriptive qualitative research design and method are utilized in the study to define student-centered learning in the classroom towards curriculum development. The study comprised thirty (30) respondents only. Results show that application of student-centered learning implements undermines demand and intention of the traditional system in teaching towards an advanced technology focus; shows that importance of student-centered learning enhances decision-making ability, problem-solving, critical thinking skills, and acquisition of new knowledge; shows that benefit of student-centered learning influences the system of curriculum development approach to identify the factors and competency in the educational system; and shows that effectiveness of student-centered learning provides opportunity for students to decide personalized learning engagement and decision-making.